Accelerated mass transfer enhancement by density-driven natural convection. Issue 3 (27th May 2022) - Has, Chandra
ABSTRACT: The prolonged heat and mass transfer can be enhanced by orders of magnitude that originate from the natural convection. This work examines the mass transfer enhancement in the fluid motion inside a horizontal capillary. In the experimental setup, dye or polystyrene (PS) in aqueous sucrose is taken on one side, and water is on the other side. The main purpose of employing two different systems (i.e. dye and PS) is that it can confirm whether the enhanced mass transfer is with only nanoparticles or it can be possible without nanoparticles in the presence of solute concentration gradients in a fluid. It is demonstrated that the induced flow is due to natural convection attributed to the density-driven flow. The induced flow in the present setup may open up various additional applications for the systems where rapid mixing is important, for instance, rapid formation of drug carriers. GRAPHICAL ABSTRACT: UF0001